La simulación frente a prácticas docentes tradicionales en la adquisición de competencias clínicas para el taller de heridas y suturas en estudiantes de medicina de la Universidad Técnica Particular De Loja en el periodo académico septiembre 2012/ febrero 2013 - Campoverde Armijos, Andrea Stephanie (2014)
The main objective of this research work was to compare outcomes between students who are educated by traditional methodology and students who have received a methodology based on simulation. The methodology used in this project was a quantitative study, descriptive design, quasi-experimental model with transverse approach. The research was conducted on students enrolled in third and seventh semester. At the students of 3er semester were taught a worshop about types of wounds and sutures and they was assessed by the OSCE while the students of 7mo semester was evaluated without receiving the simulation-based workshop. Completed work and according to the assessment scale, 3rd semester students scored higher on the acquisition of clinical skills that students 7th semester. For these reasons it is recommended that as a new methodology based on simulation because the medicine students have a better acquisition of clinical skills in comparison with the traditional methodology